2008
DOI: 10.1521/suli.2008.38.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Completed Suicide among Sinhalese in Sri Lanka: A Psychological Autopsy Study

Abstract: Sri Lanka has the one of highest rates of suicide. Important factors associated with suicide were determined via the psychological autopsy approach (which had not been carried out previously in Sri Lanka). Over a 3-month period, in a catchment area, 31 suicides among Sinhalese were identified and 27 were investigated. Males were more likely to commit suicide and alcohol abuse and domestic violence were reported as contributory factors. We found it possible to use psychological autopsy methods to obtain informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 14 publications
1
26
2
1
Order By: Relevance
“…This scale assesses the risk factors and circumstances that has been present prior to a suicide (50). This scale has been translated into Sinhala and used in an epidemiological study (51).…”
Section: Psychological Autopsy Checklistmentioning
confidence: 99%
“…This scale assesses the risk factors and circumstances that has been present prior to a suicide (50). This scale has been translated into Sinhala and used in an epidemiological study (51).…”
Section: Psychological Autopsy Checklistmentioning
confidence: 99%
“…A psychological autopsy of suicides in Finland revealed that 44% of the individuals had a previous suicide attempt (Isometsä & Lönnkvist, 1998). In Sri Lanka, 29% of individuals who died by suicide had a previous suicide attempt (Samaraweera, Sumathipala, Siribaddana, Sivayogan, & Bhugra, 2008), whereas two studies in the U.S. found that of individuals who died by suicide, 46% (Barraclough, Bunch, Nelson, & Sainsbury, 1974) and 42% of individuals had a history of suicide attempt (Conwell et al, 1998).…”
Section: Suicide Attempt As Robust Risk Factor For Eventual Death By mentioning
confidence: 99%
“…The SUPRE-MISS longitudinal follow-up study [5] reported that the repetition rate at 18 months in Sri Lanka was 4% (treatment as usual group) -substantially lower than the estimated one year repetition rate of 16% reported in the West [3,6]. In contrast, the rate of previous selfharm in those who have died by suicide in Sri Lanka has been reported to be as high as 26% [7,8].…”
Section: Introductionmentioning
confidence: 99%